Platelets and vascular integrity. (18th August 2018) - Deppermann, Carsten
Abstract: Platelets patrol the vasculature and adhere at sites of vascular damage after trauma to limit blood loss. In recent years, however, it has become clear that platelets also contribute to pathophysiologic processes such as thrombosis, atherosclerosis, stroke, sepsis and many more. An exciting new role for them is in non-classical hemostasis to prevent bleeding in the inflamed vasculature. Recent studies suggest that GPVI, CLEC-2, integrin αIIbβ3 (GPIIb/IIIa), and the content of platelet α- and dense granules are important players in this process. This review summarizes the current knowledge about how platelets prevent vascular integrity during inflammation in the skin, lung, and the ischemic brain and their organ-specific role.